Analysis of Strengthening the Regulation on the Handling of Corruption Evidence and Asset Forfeiture for the Economic Recovery of State Finances in the Perspective of Islamic Law - Abdul Saman Nst (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The handling of corruption evidence and asset forfeiture has a crucial role in efforts to restore the economy and state finances. Regulations governing this process must be strengthened to be more effective in recovering state losses and providing a deterrent effect for perpetrators. This study analyzes the strengthening of regulations related to the handling of evidence and seizure of corruption assets from the perspective of Islamic law. With a normative approach and literature study, this research compares existing regulations with the principles of Islamic law that emphasize justice, benefit, and transparency in managing the proceeds of crime. The results show that Islamic law has a concept of confiscation of illicit assets that is in line with the aim of restoring the country's economy. Therefore, strengthening regulations can be done by adopting the values of Islamic law in the national legal system to create a fairer and more effective mechanism in combating corruption.